Data Pencapaian Publikasi Ilmiah Mahasiswa Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung Tahun 2019-2023 - Wahyudin Darmalaksana; Hidayatul Fikra; Susanti Vera; Fitriani Fitriani (UIN Sunan Gunung Djati Bandung, 2024)
This research aims to display data on the publication achievements of scientific articles by students at the Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung in 2019-2023. This research uses a qualitative approach by applying data calculation methods. The results and discussion of the research show that big data on students' scientific publication achievements of 1142 is very useful for creating various categories, such as the number of achievements per year according to the distribution of study programs, achievements based on the type of scientific journal, and even the most popular keywords used by students in carrying out research. This research concludes that students' scientific publication achievements in the 2019-2023 period can be a baseline for future achievement targets.